2014
DOI: 10.1111/anae.12841
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure to anaesthetists during endovascular procedures

Abstract: SummaryMedical radiation exposure increases the likelihood of cataract formation. A personal dosimeter was attached to the left temple of 77 anaesthetists during 45 endovascular aortic aneurysm repairs and 32 interventional neuroradiology procedures. Compared with interventional neuroradiology, the median (IQR [range]) total radiation dose emitted by fluoroscopic equipment was significantly lower during endovascular aortic aneurysm repair (4175 (3127-5091 [644-9761]) mGy than interventional neuroradiology (142… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Of 52 full-text publications examined (Figure 1), 22 articles 1,13 -33 were excluded based on exclusion criteria and an additional 3 articles 34-36 that could not be assigned to an equipment group because 2 articles 34,35 failed to report the type of C-arm (mobile or fixed) and 1 article 36 reported only the primary outcomes for a mixed group use of mobile and fixed C-arms. These latter 3 studies were excluded from the meta-analysis but were included in the overall correlation plot between FT and KAP (Supplementary Table S1; supplementary material available at http://jet.sagepub.com/content/by/supplemental-data).…”
Section: Resultsmentioning
confidence: 99%
“…Of 52 full-text publications examined (Figure 1), 22 articles 1,13 -33 were excluded based on exclusion criteria and an additional 3 articles 34-36 that could not be assigned to an equipment group because 2 articles 34,35 failed to report the type of C-arm (mobile or fixed) and 1 article 36 reported only the primary outcomes for a mixed group use of mobile and fixed C-arms. These latter 3 studies were excluded from the meta-analysis but were included in the overall correlation plot between FT and KAP (Supplementary Table S1; supplementary material available at http://jet.sagepub.com/content/by/supplemental-data).…”
Section: Resultsmentioning
confidence: 99%
“…This is because fluoroscopy is used in the orthopaedic operating room with great frequency. Intra-operative imaging is used heavily during endovascular and interventional neurology operations due to their minimally invasive nature [29], but this exposure is more variable and often results in levels of radiation that are not comparable to that in orthopaedics procedures, and would not allow universal conclusions to be drawn. Although out of the scope of our review, other non-orthopaedic procedures that put anaesthetists at risk of radiation exposure may be worth further research.…”
Section: Discussionmentioning
confidence: 99%
“…At chest level, below protective garments, occupational exposure to the main operator was reported to be between 4 and 6 mSv, 10,13 while in one study it reached 15 mSv for the anaesthetists. 14 El-Sayed et al reported an occupational exposure rising to 92 mSv (range 43e203 mSv) on the unprotected part of the legs of the main operator, while median exposure to the hands was found to be up to 2105.3 mSv (826.2e4679.2 mSv) in another report. 16 Several studies investigated the exposure above the lead garments, 15e19 with levels reaching up to 1177.3 mSv (range 178.5e2134.7 mSv) at the level of the abdomen.…”
Section: Continuedmentioning
confidence: 92%